Solar cooling systems for climate change mitigation: A review. (January 2015) - Anand, S.; Gupta, A.; Tyagi, S.K.
Abstract: The impact of global warming and an increase in the indoor cooling equipments using energy sources other than conventional energy have become very attractive because they can reduce consumption of fossil fuels as well as harmful emissions in to the environment. The solar energy is one of the readily available forms of renewable energy which can be used to operate the cooling equipments depending on the geographical location of the area where solar cooling system needs to be installed. The effectiveness of solar cooling also needs to be evaluated based on various performance indicating parameters. However, different types of solar collectors also need to be evaluated in order to find out their feasibility for cooling applications. Thus in this article review of different types of solar cooling technologies have been carried out. The study reveals that evacuated tube collectors are best option for solar cooling where as desiccant cooling helps in improving the indoor air quality. Also, thermal energy storage and ejector based solar cooling efficiently improves the performance besides energy saving.